(untitled) (Journal of Asian Development Studies, 2019)
This study empirically investigates the impact of external efficiency of education system on foreign direct investment in Pakistan for the period 1984-2016. The study estimated the affect in two step estimation methodology, in first step external efficiency of education system (TE) is calculated by applying Stochastic Frontier Analysis (SFA). In the second step the estimated efficiency scores are incorporated in the time series analysis to determine the impact on FDI. The study has used Gross national income (GNI) per labor employed as output measure and mean years of schooling (MYS) along with some other explanatory measures as input to estimate external efficiency of education system. In the second step implications of education system efficiency on FDI some control measure for FDI are also incorporated, e.g. Trade openness, infrastructure, and governance. Based on unit root tests, the study follows Johansson Cointergation approach to test the cointegration among the variables. The findings of the study show that TE and MYS have positive and significant impact on FDI in Pakistan. The results are supported with standard diagnostic tests and signs of estimated coefficients are according to the expectations. Further, long run and short run estimation results are consistent with recent empirical evidence found for other countries. In case of Pakistan, no empirical study previously exists on the subject thus magnifying the contribution of this study in the literature. Based on findings of the study, it is obvious that external efficiency of education system along with traditional determinants of FDI must be considered for designing effective policies to encourage FDI inflows in Pakistan.